Perubahan Literasi Bahaya Merokok pada Siswa SMPN 4 Sumbawa - Sholihah, Nur Arifatus; Sakinah, Siti; Hamdin, Hamdin; Ratu Sepeh, Yandri (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Smoking among adolescents is a public health problem that increases the risk of non-communicable diseases. Low literacy regarding the dangers of smoking among junior high school students contributes to the high rate of early smoking initiation. This study aimed to determine changes in smoking danger literacy among students of SMPN 4 Sumbawa after interactive counseling. This research employed a pre-experimental design with a one-group pre-test and post-test approach. A total of 60 students were selected using purposive sampling. The intervention was conducted through interactive counseling using presentations, group discussions, question-and-answer sessions, and educational video screenings. The instrument used was a smoking danger literacy questionnaire covering knowledge, attitudes, and risk awareness. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of 0.05. The results showed a significant improvement in smoking danger literacy scores after the intervention (p < 0.05). Interactive counseling effectively improved smoking danger literacy among school adolescents and can be recommended as a health promotion strategy in schools